Fisher's Theory of Crises: A Criticism - England, Minnie Throop (Quarterly Journal of Economics, 1912)
The sequence of events leading up to a crisis, 95. — Interest as a factor in cost of production, 96. — A comparison of interest rates and commodity prices, 97. — Two-fold demand for loans causes rapid rise of interest, 98. — Increase in profits due to lagging behind of cost of production, 101. — Disappearance of profits due to increased cost of production, 102. — No automatic check to prosperity in rise of virtual interest rates, 104.